Between adults and children: considerations of Lina Bo Bardi’s creative process - Bierrenbach, Ana Carolina de Souza (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2008)
This paper discusses Lina Bo Bardi's creative process and compares it to her architectural creations. In order to do so, this article associates her work and the way in which adults and children behave and assimilate in the world. This association proves very useful for our understanding of Lina Bo Bardi's architecture.